2023
DOI: 10.3390/tropicalmed8040195
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Acceptability of a Strategy Deploying Multiple First-Line Artemisinin-Based Combination Therapies for Uncomplicated Malaria in the Health District of Kaya, Burkina Faso

Abstract: (1) Background: Effective malaria case management relies on World Health Organization (WHO) recommended artemisinin-based combination therapies (ACTs), but partial resistance to artemisinin has emerged and is spreading, threatening malaria control and elimination efforts. The strategy of deploying multiple first-line therapies (MFT) may help mitigate this threat and extend the therapeutic life of current ACTs. (2) Methods: A district-wide pilot quasi-experimental study was conducted, deploying three different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…These elements generated a sense of familiarity with the segmentation approach, which led to a slight preference for this deployment strategy over the other options. Similar findings were reported by Kabore et al (2023) [17] who showed that implementing MFT with a segmentation approach was operationally feasible and acceptable in Burkina Faso. In our survey, the main concern associated with the segmentation approach was a shortage of drugs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These elements generated a sense of familiarity with the segmentation approach, which led to a slight preference for this deployment strategy over the other options. Similar findings were reported by Kabore et al (2023) [17] who showed that implementing MFT with a segmentation approach was operationally feasible and acceptable in Burkina Faso. In our survey, the main concern associated with the segmentation approach was a shortage of drugs.…”
Section: Discussionsupporting
confidence: 89%
“…Authors found that the adherence by both the population and key stakeholders would depend on treatment efficacy, low severity level of side effects, cost, and drug availability. In addition, they also showed that such an intervention was operationally feasible and acceptable by stakeholders in the health system in Burkina Faso [17].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Authors found that the adherence by both the population and key stakeholders would depend on treatment efficacy, low level of side effects, cost, and drug availability. In addition, they also showed that such an intervention was operationally feasible and acceptable by stakeholders in the health system in Burkina Faso [17].…”
Section: Introductionmentioning
confidence: 98%
“…Similarly, various MFT deployment strategies have been envisaged, but none of them has been tested at scale yet. These strategies include a) rotation during which an ACT is scheduled to be used for a certain duration of time before being replaced by another one, or until a certain resistance threshold is observed; b) segmentation, where different ACTs are given to different segments of the population (pediatric, pregnant women, adults), or through different distribution channels (clinics, pharmacies, health centers); c) geographic, where different ACTs are distributed to different administrative regions [13,17].…”
Section: Introductionmentioning
confidence: 99%